Raising the Profile of HIV and AIDS in Your Parliament - Veronica Oakeshott (2016)
This guide provides practical advice for parliamentarians who wish to set up cross-party groups on HIV and AIDS in their legislatures. It accompanies the IPU-UNAIDS-UNDP Handbook for Parliamentarians, Taking action against HIV and AIDS. The Handbook is a call to action for bold parliamentary leadership, and serves as a comprehensive reference volume that legislators and their staff can consult for information and guidance on a wide range of issues relating to the epidemic.